Coulomb Stress Change of Active Fault in South Sumatra Region Revealed from Kerinci Earthquake October 06, 1995 Mw 6.7 and Sungai Penuh Earthquake October 01, 2009 Mw 6.6 - Fadhlurrohman, Rafi; Syafriani, S.; Raharjo, Furqon D.; Yusran Asnawi; Ahadi, Suaidi (Journal of Geoscience, Engineering, Environment, and Technology, 2024)
We successfully highlight the correlation of Static Stress Change (ΔCFF) in the Kerimci earthquake October 06, 1995 Mw 6.7 and Sungai Penuh earthquake October 01, 2009 Mw 6.6 earthquakes to the seismicity conditions. The data used in this study are focal mechanism obtained from Global Centroid Moment Tensor (GCMT) and seismicity obtained from USGS with M ≥ 4 after the main earthquake with a time span of 11 years. ΔCFF obtained in the Mentawai Fault System area has increased coulomb stress. ΔCFF obtained in the Suliti Segment, Ketaun Segment, and Back arc Basin of Jambi experienced an increase in stress, which can indicate the potential for future earthquakes, but there was no increase in seismicity. Besides that, ΔCFF in areas that experienced a decrease in stress, experienced an increase in seismicity. This is caused by background seismicity in the area and several factors influence the results of the calculation of ΔCFF against seismicity. Simplicity in calculation causes difficulty in explaining seismicity, especially in the blue lobe. Moreover, the use of receiver fault mechanism produces a very large error in the complex regional stress field. The use of a constant friction coefficient also produces a very large error in the calculation.